Synthesis, biological evaluation and molecular dynamics studies of 1, 2, 4-triazole clubbed Mannich bases. (October 2018) - Patel, Vatsal M.; Patel, Navin B.; Chan-Bacab, Manuel J.; Rivera, Gildardo
Graphical abstract: A series of newer analogous of triazole were synthesized by introduction of N-Mannich reaction using conventional as well as microwave synthetic route and assessed for their antimicrobial, antituberculosis and antiprotozoal activity. The computational studies revealed for that Mannich derivative showed a high affinity toward the active site of enzyme which provides a strong platform for new structure-based design efforts. Highlights: New series of N -Mannich base of 1, 2, 4-triazole was designed and synthesised. Structures of the synthesised compounds were elucidated based on spectral analysis. In vitro antiprotozoal, antimicrobial and antitubercular activities were screened. Structure activity relationship has been determined. Molecular docking and Molecular dynamics simulation studies were performed. Abstract: The present work highlightsthe synthesis of a newer biologically active Mannich bases contributing 4-((4-fluorobenzylidene)amino)-5-(pyridin-4-yl)-4 H -1, 2, 4-triazole-3-thiol and various heterocyclic amines via N -Mannich reaction by the conventional method as well as microwave heating approach as a part of an environmentally benign synthetic protocol. All the synthesized compounds were characterized by spectral analysis and were screened for in vitro antimicrobial, antitubercular and antiprotozoal activity. The compound 4k was found to be most active respectively against S. aureus (MIC 12.5 μM) and C. albicans (MIC 100 μM). The derivative 4 g displayed potency against L.mexicana and T. cruzi with IC50 value 1.01 and 3.33 μM better than reference drug Miltefosina and Nifurtimox. The compound 4b displayed excellent potency against M. tuberculosis (MIC 6.25 μM) in the primary screening. The computational studies revealed for that Mannich derivative (4b) showed a high affinity toward the active site of enzyme which provides a strong platform for new structure-based design efforts. The Lipinski's parameters showed good drug-likeness properties and can be developed as an oral drug candidate.